Perkembangan Bank Syariah Di Indonesia: Sebuah Kajian Historis - M. Dliyaul Muflihin (Universitas Islam Lamongan, 2019)
Banking in Indonesia is now increasingly enlivened by the existence of Islamic banks, which offer financial and investment products in different ways than conventional banks that have long existed. Even conventional banks in Indonesia are now following the trend by establishing their own Islamic institutions or Islamic business units. Recorded in 2012 Islamic banks have increased rapidly to become 11 Islamic Commercial Banks (BUS) and 24 Sharia Business Units (UUS). Islamic banks were born and developed in Indonesia starting from the birth of Bank Muamalat in 1992. Law Number 7 of 1992 concerning banking was born because in that year Bank Muamalah was the only bank that carried out business activities based on the principle of profit sharing. Furthermore, the culmination point has been reached with the enactment of Law Number 10 of 1998 concerning banking which opens the opportunity for anyone who will establish a Shari'ah bank or who wants to convert from a conventional system to a sharia system. Until the issuance of Law No.10 of 1998. Furthermore, Law No.10 of 1998 was amended by Law No. 21 of 2008 concerning Islamic banking because on June 17 2008 the Law on Islamic Banking was adopted which promulgated in the State Gazette on July 16 2008. Keywords: History of Development, Islamic Banking, Indonesia